1998
DOI: 10.1203/00006450-199804001-00799
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for and Long-Term Outcome of Ifosphamide-Induced Nephrotoxicity in Children † 778

Abstract: Ifosfamide is widely used in the treatment of pediatric solid tumors. Its main adverse effects are various forms of renal tubular and glomerular damage. The authors sought to determine factors that predict the risk for the development and severity of ifosfamide‐induced nephrotoxicity in children and to examine the long‐term outcome of this complication. A total of 174 children who had received ifosfamide for various cancers were studied. Nephrotoxicity was assessed by laboratory markers of glomerular and tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
119
2
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(128 citation statements)
references
References 17 publications
4
119
2
3
Order By: Relevance
“…3,4). Recent reports have shown that the frequency of renal damage is remarkably higher than had been appreciated, and IFO-induced nephropathy is likely underestimated because of the inherent flaws in the evaluation methods commonly used and the time dependence of IFO-induced nephrotoxicity (6,7,9). This is especially true in cases of lateonset glomerular dysfunction (5,6,9).…”
Section: Introductionmentioning
confidence: 85%
“…3,4). Recent reports have shown that the frequency of renal damage is remarkably higher than had been appreciated, and IFO-induced nephropathy is likely underestimated because of the inherent flaws in the evaluation methods commonly used and the time dependence of IFO-induced nephrotoxicity (6,7,9). This is especially true in cases of lateonset glomerular dysfunction (5,6,9).…”
Section: Introductionmentioning
confidence: 85%
“…58 Ifosfamide can induce renal tubulopathy/Fanconi syndrome, and may subsequently manifest as hypophosphatemic rickets, compromising bone structure. 59 Due to hypercoagulability, vascular endothelial damage, and disruption of bone formation, purine antimetabolites can impair proliferation of chondrocytes.…”
Section: Nonglucocorticoid Drugsmentioning
confidence: 99%
“…Chemotherapeutic agents with well documented early nephrotoxicity are ifosfamide, cisplatin, and carboplatin (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%